McDonald Seksyen 7 Shah Alam / Nadia Athira Yunus ... [et al.] - Yunus, Nadia Athira; Nik Baharudin, Nik Nurfadzillah; Sabri, Nur 'Atikah; Azman, Nurul Haziqah; Abu Bakar Sonny, Nurul Najwa Zulaikha; Nahar, Zulemalina (2019)
This case study is conducted to analyze the real situation of technopreneurship. On this case study, we have chosen McDonalds, Section 7 Shah Alam to conduct our investigation. McDonald have been~a~well-known as one of the leading restaurant chains in the world. Their main purpose is to focus on all types of customer where their target market is for everyone in the community around the world. The purpose of this study is to analyze the strategies, strength and weaknesses which McDonald's have been dealt with. All these factors will be discussed further in the case study.